KONSELING KELOMPOK DENGAN TEKNIK COGNITIVE RESTRUCTURING UNTUK MEREDUKSI KETERLAMBATAN PESERTA DIDIK - Amelia S, Tri Putri; Silvianetri, Silvianetri (Realita : Jurnal Bimbingan dan Konseling, 2023)
The purpose of this study was to determine the factors of student delays, follow-up by homeroom teachers, guidance counselors and students as well as the school's efforts to renew school rules regarding sanctions for late students arriving at school. The type of research used is qualitative research using the case study method. In this case study research the data collection techniques used were observation and interviews. The data analysis used was triangulation, both source triangulation and technique triangulation. Data on tardiness was collected through anecdotal notes for each counseling teacher. The research subjects were 9 students who had the highest intensity of lateness at school. To reduce student delays through counseling guidance services, group counseling with cognitive restructuring techniques is considered effective in overcoming these problems. The results of the study showed that 7 students showed very good changes seen through a decrease in the level of lateness to school and tended not to repeat the same behavior. Meanwhile, 2 students need to be assisted with individual counseling and home visits